Retroactive effect of unconstitutional judgment - سوز حمید مجید (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
There is no need to add to the binding force of a decision of unconstitutionality against all powers of the government, the issue normally reflects on retroactive affects of that decision. With this regard, the law that is subjected to constitutional review is considered void since its issuance, therefore the decision to declare its unconstitutionality leaves affects on the stability of legal statuses that earned prior to the decision and also on the legal security. It is worth mentioning that the decision of unconstitutionality neither abolish nor amend the concerned legal text because this authority is exclusively reserved by the power issued the law otherwise it contradicts the principle of separation of powers. The fact that the Federal Supreme Court does not have power to abolish the law also means that it does not have power to amend it because there are specific procedures in the Iraqi Constitution that need to be followed for any amendment.